A Bibliometric Analysis of the Top Cited Articles in Sports and Exercise Medicine. Issue 1 (22nd January 2021) - Khatra, Omeet; Shadgan, Armita; Taunton, Jack; Pakravan, Amir; Shadgan, Babak
Background: Although citation analysis is common in many areas of medicine, there is a lack of similar research in sports and exercise medicine. Purpose: To identify and examine the characteristics of the 100 top cited articles in the field of sports and exercise medicine in an effort to determine what components make an article highly influential. Study Design: Cross-sectional study. Methods: The Web of Science, Scopus, and PubMed databases were used to determine the 100 top cited articles from 46 journals in the field of sports and exercise medicine. Each of the 100 articles was then analyzed by 2 independent reviewers, and results were compared. Basic information was collected, including journal title, country of origin, and study type. Different categories were compared using descriptive statistics of counts or percentages. Results: The 100 top cited articles were published in 15 of the 46 identified sports and exercise medicine journals, with the most prolific being Medicine and Science in Sports and Exercise (n = 49), American Journal of Sports Medicine (n = 18), and Sports Medicine (n = 7). In terms of country of origin, the top 3 contributors were the United States (n = 65), Canada (n = 9), and Sweden (n = 8). The most commonly researched anatomic areas were the knee (n = 15) and the brain (n = 3). Narrative reviews were the most common study type (n = 38), and only a single study on the 100 top cited articles list used a randomized controlled trial design. The most prevalent fields of study were exercise science (55% of articles) and well-being (16% of articles). Conclusion: Narrative reviews from the United States and published in English-language journals were the most likely to be highly cited. In addition, the knee was a common anatomic area of study on the top cited list of research in sports and exercise medicine